Kontribusi Pemikiran Linguistik al-Anbari Terhadap Penafsiran Kosa Kata Kontranimi - Mahyudin Ritonga (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2018)
This paper wants to describes the contribution of al-Anbari's thought in the interpretation of the verses of the Koran, this is inseparable from al-Anbari's expertise not in the field of interpretation but linguists. The main source of this research is the work of al-Anbari entitled